Assessment of child's dental anxiety/fear and stress during dental treatment: a systematic review by CEDACORE - Heloisa de Sousa Gomes; Anna Alice Anabuki; Karoline Alves Viana; Lucas Guimarães Abreu; Aline Carvalho Batista; Marie Therese Hosey; Luciane Rezende Costa (Sociedade Brasileira de Pesquisa Odontológica, 2022)
Abstract: There is a lack of evidence on the correlation between salivary biomarkers and subjective measures of dental fear and anxiety in children. This systematic review aimed to retrieve the scientific evidence comparing the results of dental anxiety measured by salivary biomarkers with patient-reported outcomes in pediatric dental setting. The PECOS was as follows: population: pediatric patients aged ≤ 18 years; exposure: patient-reported outcome measures, such as scales and/or questionnaires; comparator: salivary biomarkers; outcome: anxiety, fear, phobia or stress during dental treatment; study design: observational studies or controlled trials. Electronic searches were conducted in PubMed, Scopus, Web of Science, and Ovid databases. Studies that compared scales/questionnaires and salivary biomarkers for the evaluation of dental anxiety, fear, and stress in children/adolescents during dental treatment were included. Certainty of evidence was assessed with GRADE. Risk of bias of the included studies was assessed with the Cochrane tool or the University of Adelaide tool. From the 314 studies identified, eight were included. Participants' age ranged from three to 13 years. The most used salivary biomarkers and instruments were cortisol and the Dental Subscale of the Children's Fear Survey Schedule, respectively. Most studies showed a weak correlation between objective and subjective measures. The main issues regarding bias were on allocation concealment, blinding of assessors, follow up, and exposure assessment. Certainty of evidence was low/very low. Evidence of salivary biomarkers and patient-reported outcome measures to investigate anxiety, fear and stress in children during in the dental environment is limited. There was no correlation between subjective and objective measures in almost all included studies.